Synthesis of Asymmetrically Substituted Terpyridines by Palladium‐Catalyzed Direct CH Arylation of Pyridine N‐Oxides. Issue 51 (13th November 2013) - Duric, Sasa; Sypaseuth, Fanni D.; Hoof, Santina; Svensson, Emma; Tzschucke, C. Christoph
Abstract The synthesis of asymmetrically substituted 2, 2′:6′, 2′′‐terpyridines is reported. First, palladium‐catalyzed CH arylation of pyridine N‐oxides with substituted bromopyridines gave 2, 2′‐bipyridine N‐oxides, which were further arylated in a second step to form 2, 2′:6′, 2′′‐terpyridine N‐oxides. Yields of up to 77 % were obtained with N‐oxides bearing an electron‐withdrawing ethoxycarbonyl substituent in the 4‐position. Pd(OAc)2 with either P(tBu)3 or P(o‐tolyl)3 was used as the catalyst. Cyclometalated complexes derived from Pd(OAc)2 and these phosphines were also effective. K3PO4 as the base gave better results than K2CO3. Subsequent deoxygenation with H2 and Pd/C as the catalyst gave the asymmetrically substituted 2, 2′:6′, 2′′‐terpyridines in near quantitative yield. This reaction sequence significantly reduces the number of steps required in comparison with known cross‐coupling methods and therefore allows convenient and scalable access to substituted terpyridines.